TANTANGAN SANTRI DI ERA DIGITAL - kusmawati (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
The digital era has brought significant transformations in human life. The use of technology in the digital era is increasingly widespread in various sectors such as education, economy, health, agriculture and government. For santri in Indonesia, who are the digital native generation, the challenges of the digital era have a special impact. This research aims to discuss the challenges faced by santri in the digital era and focuses on the abilities that santri must have to be able to compete in the digital era. The study shows that challenges arise in the form of unequal access and use of technology, digital content that is not in accordance with religious norms, customs and decency, interference with worship, and threats to personal security and privacy. To be able to adapt to technological advances in the digital era, santri must have competencies such as digital literacy, creativity, adaptability, visionary and integrity. In addition, choosing the right educational institution and mastering foreign languages are significant factors. With adequate knowledge and skills, santri will be able to face competition in the digital era.